Juvenile Murderers: Is It the Impact of Dark Triad Personality or Lead Poisoning? A Comparative Study - Rahayu, Yusti Probowati; Setiawan, Vendra; Manafe, Rizky Pradita; Indrajati Kohar (Universitas Ahmad Dahlan, 2025)
This study contributes by integrating psychological and pharmacological perspectives in understanding juvenile murderers. This is a comparative study that compares DTP and Pb between juvenile murderers and non-criminal juveniles. The participants were 7 juvenile murderers and 7 non-criminal juveniles. Inductively coupled plasma optical emission spectroscopy was used to examine Pb levels in hair. A modified Paulhus and William DTP questionnaire was applied to all participants. Qualitative data used interview and drawing test on juvenile murderers. Quantitative data on murderous and non-criminal juveniles for DTP used T Test and Pb were analyzed with the Mann-Whitney U test. Correlation between DTP and Pb used Pearson Correlation. Qualitative analyzed used thematic content analysis. Results revealed that there are has significant differences on Pb between JM and NCM. Pb levels in juvenile murderers were higher than those in noncriminal ones. There is no difference between juvenile murderers and noncriminal ones, according to DTP. However, descriptive statistics revealed that adolescent murderers typically had higher DTP than noncriminal ones. Based on the structural interview and psychological drawing test, juvenile murderers tend to have DTP characteristics. Spearman correlation showed that there was no correlation between Pb and DTP noncriminal adolescents. Further research is needed with more precise and comprehensive methods to find out the causes of teenagers committing murder, one of them is qualitative approach. Integration with pharmaceuticals remains necessary because juvenile murder cannot be explained solely by a psychological approach.